2021
DOI: 10.3390/ijms22084112
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine-Induced Peripheral Neuropathy (VIPN) in Pediatric Tumors: Mechanisms, Risk Factors, Strategies of Prevention and Treatment

Abstract: Vincristine-induced peripheral neurotoxicity (VIPN) is a very common side effect of vincristine chemotherapy among pediatric patients with cancer. Neuropathy may be sensory, motor and/or autonomic, with consequent reduction, delay or discontinuation of vincristine-chemotherapy, but also pain, disability, reduced quality of life of patients and an increase in medical costs. Vincristine acts out its antineoplastic function by altering the normal assembly and disassembly of microtubules, with their consequent mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 78 publications
0
72
0
10
Order By: Relevance
“…Chemotherapy-induced peripheral neuropathies (CIPN) are a set of clinical conditions observed in patients administered with chemotherapeutics. CIPN commonly occurs as an undesirable, dose-limiting effect of several chemotherapeutics such as cisplatin, paclitaxel [ 143 , 144 ], vinblastine, and vincristine [ 145 ], mainly due to chemically induced damage to axons and cell bodies of peripheral neurons. Though the underlying mechanism of CIPN is not completely known, axonal degeneration or ‘dying back’ is a well-recognized histopathological hallmark [ 27 , 146 ], and understanding the molecular mechanism behind such pathogenesis is crucial to develop therapeutic strategies.…”
Section: Chemically Induced Nerve Injury Modelsmentioning
confidence: 99%
“…Chemotherapy-induced peripheral neuropathies (CIPN) are a set of clinical conditions observed in patients administered with chemotherapeutics. CIPN commonly occurs as an undesirable, dose-limiting effect of several chemotherapeutics such as cisplatin, paclitaxel [ 143 , 144 ], vinblastine, and vincristine [ 145 ], mainly due to chemically induced damage to axons and cell bodies of peripheral neurons. Though the underlying mechanism of CIPN is not completely known, axonal degeneration or ‘dying back’ is a well-recognized histopathological hallmark [ 27 , 146 ], and understanding the molecular mechanism behind such pathogenesis is crucial to develop therapeutic strategies.…”
Section: Chemically Induced Nerve Injury Modelsmentioning
confidence: 99%
“…Oxaliplatin accumulates in dorsal root ganglion neurons and causes functional changes in nerve excitability to undergo severe neuropathy [ 63 ]. Vincristine determines a compromission of microtubule function and axonal transport with mitochondrial toxicity [ 7 , 64 ]. Another pathway observed in the chemotherapeutic drugs neurotoxicity is the stimulation of NK cells by upregulation of stress related proteins in tumor and/or downregulation of inhibitory self-ligands on the target cell surface [ 65 , 66 , 67 ].…”
Section: Dinutuximab Induced Peripheral Neuropathymentioning
confidence: 99%
“…The treatment strategy for high-risk neuroblastoma patients includes induction chemotherapy, surgery, consolidation with myeloablative high-dose chemotherapy (HDT) followed by autologous stem cell transplantation (SCT), and maintenance therapy. Better tumor responses after induction therapy appear to be critical to improve the percentage of long-term survival, but the dose intensity of traditional drugs such as platin compounds, cyclophosphamide, etoposide, doxorubicin, vincristine, topotecan, and temozolomide cannot be increased because of their hematological and non-hematological toxicities [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Moreover, some new combinations of agents active against neuroblastoma have been developed with encouraging results, but none of them have yet been adopted in large randomized trials [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the potential neuroprotective agents, the only ones that have been trialed in the pediatric population are carbamazepine, glutamic acid and amifostine for the prevention of CIPN, and intravenous immunoglobulin, pyridoxine/pyridostigmine and gabapentin for treatment, with limited evidence (Level C) for benefit [ 3 ]. However, in a recent review of VIPN (probably, the most well studied CIPN in the pediatric population) has been reported that pyridoxine and pyridostigmine may induce an improvement in symptoms while glutamic acid and glutamine may have a good preventive role [ 113 ].…”
Section: Chemotherapy-induced Peripheral Neuropathy (Cipn)mentioning
confidence: 99%